Applied communication research methods getting started as a researcher - Boyle, Michael P. 1975-; Schmierbach, Mike 1976- (New York, NY Routledge, an imprint of the Taylor & Francis Group, 2020)
"A hands-on guide for applying research methods to common problems, issues, projects, and questions that communication practitioners deal with on a regular basis, this text demonstrates the relevance of research in professional roles and communication careers. The second edition features updated material that covers major communication research methods including surveys, experiments, focus groups, observation research, while also providing key background information on ethics, validity, reliability, concept explication, statistical analysis, and other current topics. It continues to foster student engagement with research through its numerous features and practical activities, including: Research in Depth - examples of methods as applied in scholarly research, Reflect and React - problems and issues that promote reflection and discussion, Voices from Industry - Q&As with professionals working in communication industries, End-of-unit activities - exercises that reinforce concepts and content The text is ideally suited to both undergraduate and graduate courses in mass communication research methods. Online resources, including sample syllabi, PowerPoint slides, and test banks are available on the companion website: www.routledge.com/cw/boyle."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Communication -- Research; Communication -- Methodology